Pemberdayaan Literasi Dan Numerasi Untuk Meningkatkan Prestasi Siswadi Sd Negeri 17 Tanjung Selamat - Tri Indah Rezeki; Irwan, Irwan; Sagala, Rakhmat Wahyudin; Rabukit, Rabukit; Ningsih, Euis Indah Kesuma (Yayasan Literasi Sains Indonesia, 2024)
The literacy and numeracy empowerment program implemented at SD Negeri 17 Tanjung Selamat was designed to directly address the challenges faced by students in essential reading, writing, and mathematics skills. The program was developed with an active learning approach that prioritizes direct student engagement through various innovative teaching methods. In addition, the program also emphasizes the use of media and technology to enrich the teaching and learning process and involvearents and the community in creating a holistic and supportive educational environment. The methods used include teacher training, provision of learning aids and interactive programs designed to motivate students.The program results showed significant improvements in students' literacy and numeracy skills, with better test scores after the program was implemented. Teachers and parents also engaged more, creating a supportive and holistic learning environment. Technology has proven effective in making learning more exciting and interactive. At the same time, community support helps enrich educational resources. In conclusion, the program has succeeded in improving the quality of education at SD Negeri 17 Tanjung Selamat through a comprehensive and collaborative approach, providing a solid foundation for students' academic development and critical thinking skills